2020
DOI: 10.1101/2020.10.20.20215905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical characteristics of 4490 COVID-19 patients in Africa: A meta-analysis

Abstract: Introduction: The novel coronavirus disease-2019 (COVID-19) pandemic that started in December 2019 has affected over 39 million people and killed over 1.1 million people. While more studies are published to help us understand the virus, there is a dearth of studies on the clinical characteristics and associated outcomes of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) on the African continent. Methods: We evaluated evidence from previous studies in Africa available in six databases between J… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…16 Similar findings were reported from a meta-analysis of clinical characteristics of covid-19 patients in Africa where clinical outcomes directly correlate with the underlying medical conditions and age. 17 Furthermore, this high mortality rate amongst the elderly with comorbidity was also reported from many international studies from France, the United Kingdom and Germany in the same age groups. 12,18 Our data also indicated that the majority of COVID-19 hospitalised patients who died during this period had underlying medical comorbidity and one-third of them died either on arrival to the hospital or within 1 h of arrival.…”
Section: Discussionsupporting
confidence: 69%
“…16 Similar findings were reported from a meta-analysis of clinical characteristics of covid-19 patients in Africa where clinical outcomes directly correlate with the underlying medical conditions and age. 17 Furthermore, this high mortality rate amongst the elderly with comorbidity was also reported from many international studies from France, the United Kingdom and Germany in the same age groups. 12,18 Our data also indicated that the majority of COVID-19 hospitalised patients who died during this period had underlying medical comorbidity and one-third of them died either on arrival to the hospital or within 1 h of arrival.…”
Section: Discussionsupporting
confidence: 69%
“…Patients presented with the typical symptoms of COVID-19 that have also been reported elsewhere in Africa. 20 Fever, however, was only found in 12% of patients and many patients had hyperglycaemia and high blood pressure, reflecting underlying comorbidities. Family physicians reported that the procedures to use infrared thermometers to triage patients may not have resulted in accurate measurements and therefore fever may be underobserved.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil ini sesuai dengan beberapa penelitian lainnya yang menunjukkan bahwa batuk dan demam merupakan keluhan yang paling sering. 20,21,30 Hasil analisis bivariat (Tabel 2) dan analisis multivariat (Tabel 3) menunjukkan bahwa terdapat hubungan yang signifikan antara demam dengan lama rawat inap. Hal ini konsisten dengan penelitian oleh Guo, dkk.…”
Section: Hasilunclassified